การคัดแยกแบคทีเรียจากน้ำย้อมครามในหม้อย้อมและดินบริเวณย้อมครามเพื่อประยุกต์ใช้ในการย้อมและบำบัดน้ำเสีย - สุขขะ, กันต์กนิษฐ์; สมปาก, เฉลิมวุธ; ธนานันต์, ธีระชัย; ศากยวงศ์, นิรมล; เจียรนัยกุล, นิชาดา (Thai Journal of Science and Technology, 2019)
Abstract Bacterial strains from natural indigo dyeing process at indigo-dyed pots and dyeing soil were isolated and identified, for application of the dyeing process and decolorizing in wastewater treatment. By analyzing morphological and molecular characteristics with 16S rRNA genes sequence, the 23 isolated bacteria were classified into 5 genera, i.e. Bacillus (15 isolates), Pseudomonas (4 isolates), Acinetobacter (2 isolates), Lysinibacillus (1 isolate), and Aerococcus (1 isolate). A preliminary study demonstrated that bacteria in the indigo-dyed pot could change indican to indoxyl and glucose. The results showed that Bacillus kochii SKTU5 was able to produce 63.67±6.59 mM glucose at 30 ºC for 96 hours. However, Acinetobacter baumannii SKBT2, the isolated soil bacteria from the dyeing area, could decolorize the indigo dye as 79.13±0.43 % at the original concentration of 25 mg/L, under the static condition at 37 ºC for 48 hours. These results can be further applied to create the starter seeds for indigo dyeing process and decolorizing indigo dye in wastewater treatment. Keywords: natural indigo dyeing process; decolorization; indigo dye; 16S rRNA gene